Implementation of Islamic Religious Education Learning at MI Negeri 2 reviewed from the perspective of Objectives, Principles, Methods, and Evaluation - Radhiah; Riskia (Journal of Indonesian Primary School, 2025)
This study aims to analyze the implementation of Islamic Religious Education (PAI) learning in Madrasah Ibtidaiyah Negeri 2 by reviewing aspects of objectives, principles, methods, and evaluation. The background of this research is the importance of PAI in forming students who not only understand religious material theoretically, but are also able to internalize and practice it in daily life. This research uses a qualitative approach with literature study methods and content analysis. Data were obtained from school documents, observation of learning activities, and relevant literature. The results of the study show that the implementation of PAI in MIN 2 runs according to the established procedures, by prioritizing scientific principles, monotheism, practice, and habituation of noble morals. The learning methods used are diverse, including group work, discussions, simulations, role-playing, and the use of contextual media. Learning evaluation is carried out comprehensively through written, oral, and practical tests, and emphasizes the achievement of students' cognitive, affective, and psychomotor competencies. Overall, the results of the study show that the implementation of PAI learning at MIN 2 is effective in helping students understand and internalize the values of Islamic teachings. Thus, the learning model applied in MIN 2 can be a reference in the development of PAI learning at the elementary level.